Evaluating the Effectiveness of a Gamified Learning Approach in Digital Marketing: A Quasi-Experimental Study - Kurniasih, Tatit (Pusat Standar dan Kebijakan Pendidikan, BSKAP, Kemendikbudristek, 2025)
This study aims to evaluate the effectiveness of the educational board game Digital Marketing Tycoon (DMT) in enhancing high school students’ understanding of digital marketing concepts. Using a quasi-experimental pretest–posttest design, 345 students from Semarang and Jakarta were divided into an experimental group (n = 177) and a control group (n = 168). The experimental group played DMT for 60–90 minutes, while the control group received conventional instruction. Data were collected through a validated 20-item online quiz (Cronbach’s a = .82) administered before and after the intervention. Paired-samples t test revealed a significant improvement in the experimental group (mean increase = 13.94 points), with a large effect size (Cohen’s d = 1.55). The control group showed minimal change. A Shapiro–Wilk test confirmed the normality of the data. A strong positive correlation (r = .640, p < .001) indicated consistent learning gains across all ability levels. Qualitative observations indicated increased engagement, collaboration, and strategic thinking. The findings support the integration of purpose-designed board games into entrepreneurship curricula to bridge abstract concepts with real-world application. Recommendations include piloting Digital Marketing Tycoon within national curriculum frameworks, providing teacher training in gamification, and conducting longitudinal studies to assess long-term knowledge retention.